Protecting Divorced Muslim Women’s Rights through Maintenance: A Comparative Analysis based on the Present Legislative Reforms among the Muslim Community - Aktar, Sharmin (Northern University Journal of Law, 2014)
DOI: http://dx.doi.org/10.3329/nujl.v3i0.18393 Northern University Journal of Law Vol.III 2012; p.23-48